Hubungan Tingkat Stres dengan Keparahan Akne Vulgaris Pada Pelajar Putri Madrasah Aliyah Negeri I Yogyakarta - Jusuf, Muhammad isman (Jurnal Pelangi Ilmu, 2009)
Background: Acne vulgaris is a chronic folikel pilosebasea inflamation skin disease. This often happens to adolescent. For adolescent pubercity become a central concern during their psysiological development, marked by increase in hormonal secretion, particularly sex hormone, and stressfull conflicted ages. It is not surprising if those conflicts become one of the factors causing ane vulgaris to adolescent. Objective: This study aims to find out the correlation between stress and acne vulgaris to Madrasah Aliyah Negeri I Yogyakarta female students. Methods: This is a crossectional study. Data are taken from Madrasah Aliyah Negeri I Yogyakarta female students, with consecutive sampling. Research is conducted with questioner. Result: From 70 respondent, there were 24,3% resistant to stress, 91,4% suffered psychosocial stressor with varying degrees and 55.7% suffered anxiety with vaying degrees.100% of respondent suffered non inflammatory lesions. After statistical analysis with pearson correlation, p